Stable isotope ecology and interspecific dietary overlap among dolphins in the Northeast Atlantic - Plint, Tessa; ten Doeschate, Mariel T.I.; Brownlow, Andrew C.; Davison, Nicholas J.; Hantke, Georg; Kitchener, Andrew C.; Longstaffe, Fred J.; McGill, Rona A. R.; Simon-Nutbrown, Cornelia; Magill, Clayton R. (Frontiers in Marine Science, 2023)
Dolphins are mobile apex marine predators. Over the past three decades, warm-water adapted dolphin species (short-beaked common and striped) have expanded their ranges northward and become increasingly abundant in British waters. Meanwhile, cold-water adapted dolphins (white-beaked and Atlantic white-sided) abundance trends are decreasing, with evidence of the distribution of white-beaked dolphins shifting from southern to northern British waters. These trends are particularly evident in Scottish waters and ocean warming may be a contributing factor. This mobility increases the likelihood of interspecific dietary overlap for prey among dolphin species previously separated by latitude and thermal gradients. Foraging success is critical to both individual animal health and overall population resilience. However, the degree of dietary overlap and plasticity among these species in the Northeast Atlantic is unknown. Here, we characterise recent (2015-2021) interspecific isotopic niche and niche overlap among six small and medium-sized delphinid species co-occurring in Scottish waters, using skin stable isotope composition (δ13C and δ15N), combined with stomach content records and prey δ13C and δ15N compiled from the literature. Cold-water adapted white-beaked dolphin have a smaller core isotopic niche and lower dietary plasticity than the generalist short-beaked common dolphin. Striped dolphin isotopic niche displayed no interspecific overlap, however short-beaked common dolphin isotopic niche overlapped with white-beaked dolphin by 30% and Atlantic white-sided dolphin by 7%. Increasing abundance of short-beaked common dolphin in British waters could create competition for cold-water adapted dolphin species as a significant portion of their diets comprise the same size Gadiformes and high energy density pelagic schooling fish. These priority prey species are also a valuable component of the local and global fishing industry. Competition for prey from both ecological and anthropogenic sources should be considered when assessing cumulative stressors acting on cold-water adapted dolphin populations with projected decline in available habitat as ocean temperatures continue to rise.